2006
DOI: 10.1073/pnas.0511244103
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced dendritic spine formation in D1 and D2 dopamine receptor-containing medium spiny neurons in nucleus accumbens

Abstract: Psychostimulant-induced alteration of dendritic spines on dopaminoceptive neurons in nucleus accumbens (NAcc) has been hypothesized as an adaptive neuronal response that is linked to longlasting addictive behaviors. NAcc is largely composed of two distinct subpopulations of medium-sized spiny neurons expressing high levels of either dopamine D1 or D2 receptors. In the present study, we analyzed dendritic spine density after chronic cocaine treatment in distinct D1 or D2 receptor-containing medium-sized spiny n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
315
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(348 citation statements)
references
References 64 publications
29
315
3
1
Order By: Relevance
“…Interestingly, a trend toward a bimodal distribution is observed in mEPSC frequency. This could reflect differing effects of amphetamine within subpopulations of MSNs that express either DA D1 or D2 receptors, which have been observed with repeated cocaine exposure (Lee et al, 2006;Lobo et al, 2010;Pascoli et al, 2012) Together, these results demonstrate that in contrast to amphetamine's region-specific effect (shell only), cocaine induces bidirectional AMPAR plasticity in MSNs in both NAc shell and core.…”
Section: In Vivo Amphetamine Induces Bidirectional Plasticity In Synamentioning
confidence: 57%
“…Interestingly, a trend toward a bimodal distribution is observed in mEPSC frequency. This could reflect differing effects of amphetamine within subpopulations of MSNs that express either DA D1 or D2 receptors, which have been observed with repeated cocaine exposure (Lee et al, 2006;Lobo et al, 2010;Pascoli et al, 2012) Together, these results demonstrate that in contrast to amphetamine's region-specific effect (shell only), cocaine induces bidirectional AMPAR plasticity in MSNs in both NAc shell and core.…”
Section: In Vivo Amphetamine Induces Bidirectional Plasticity In Synamentioning
confidence: 57%
“…Studies of cocaine's effects in the NAc have shown dopamine receptor 1 (D 1 R)-expressing cells to be the primary longterm locus of spine change (Lee et al, 2006;Lobo et al, 2010), and as mentioned above, IkK is a potent regulator of spine density in this region. IkK activity in response to stress or stimulant administration may similarly be regulated in a cell-type-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, its induction in NAc by antidepressants is required for the therapeutic-like effects of these drugs (Vialou et al, 2010). Although DFosB is known to affect both the morphology (Lee et al, 2006;Maze et al, 2010;Robison et al, 2013) and synaptic physiology (Grueter et al, 2013) of NAc medium spiny neurons, identification of its specific mechanisms of action and gene targets remains a goal for the field.…”
Section: Introductionmentioning
confidence: 99%